Chemical Composition, Antitumoral and Antibacterial Activities of Essential Oils from Leaves and Stem Bark of Nectandra lanceolata (Lauraceae). Issue 5 (3rd September 2017) - Costa, Érica R.; Louro, Gabriela M.; Simionatto, Simone; Vasconcelos, Nathalie G.; Cardoso, Claudia A.L.; Mallmann, Viviane; da Silva, Rogério C.L.; Matos, Maria de F.C; Pizzuti, Lucas; Santiago, Etenaldo F.; Morel, Ademir F.; Mostardeiro, Marco A.; et al.
Abstract: The essential oil of leaves and barks of Nectandra lanceolata, obtained by hydrodistillation, was characterized in terms of its chemical composition by GC-FID, GC-MS and NMR. The analyses and identiûcation pointed by mass fragmentation pattern and retention index revealed the presence of 30 compounds in the oil from leaves and 36 compounds in oil from barks, representing 91.8 % of the total leaf oil and 96.5 % of the bark oil. The major compounds of the leaf oil were E -caryophyllene (12.45 %), biciclogermacrene (18.2 %) and spathulenol (16.7 %). In the oil from barks, the major compounds were guaiol (13.2 %), cubenol (7.6 %), α- epi-cadinol (4.8 %), γ-cadinene (7.6 %), α-pinene (6.9 %). Moreover, were evaluated the potential of inhibition against the resistant bacteria Acinetobacter baumannii and antitumor properties of oils. It was possible to conclude that oil from bark of Nectandra lanceolata present more potent activity than oil from leaves. The essential oil from bark of Nectandra lanceolata showed more activity against K562 (14.6 μg.mL -1 ) and U251 (37.3 μg.mL -1 ). The content of these fractions was predominantly of the sesquiterpenes, such as guaiol, cubenol, 1-epi-α-cadinol and caryophyllene oxide, which were enriched after fractio-nation. These fractions were tested in vitro against two human cancer cell lines (786-0 and HT-29) by Sulforhodamine B assay, showing improved activity when compared to the crude oil. The bark oil showed activity against resistant bacteria Acinetobacter bamanni with an inhibition zone of 18 mm and MIC value of 18 mg.mL -1 .